Kualitas Biopelet Cabang Kayu Kawui (Vernonia arborea Buch.Ham) Menggunakan Tiga Level Persentase Perekat : Quality of Bio-pellets from Kawui Wood Branches (Vernonia arborea Buch.Ham) Using Three Levels of Adhesive Percentage - Indrayanti, Lies; Siska, Grace; Luhan, Gimson; Jesica, Irma (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
The research aims to determine the quality of bio-pellets from Kawui wood branches using three levels of adhesive percentage. The materials used are branch wood from Kawui and tapioca flour adhesive. The research method employs a Completely Randomized Design with a single factor, namely the adhesive percentage. The factor consists of three levels: adhesive percentages of 10%, 20%, and 30%, with five repetitions. The results indicate that the adhesive percentage does not significantly affect the ash content, volatile matter content, and fixed carbon content, except for calorific value and density. The quality of bio-pellets meets the SNI 8675-2018 standard for household and industrial scales at all adhesive percentages, except for volatile matter content and fixed carbon content. According to French standards, the quality of bio-pellets meets the standards for every parameter except calorific value at the 30% adhesive percentage. According to Swedish standards, the quality of bio-pellets meets the standards for every parameter except moisture content at the 10% adhesive percentage and calorific value at the 30% adhesive percentage. Overall, the 20% adhesive percentage exhibits the best quality